Goya, a free man, Royal Academy of Medicine and Surgery of Valladolid for the Meeting of the three Royal Academies of Valladolid. May 16, 2019. (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
Goya is characterized by its appreciation for freedom, he is first and foremost a free man. The subtitle of the talk “Paintings for an exhibition” is timely, the corpus of our conference contains personal comments on the different works created by Goya. His paintings on women, children and families are analyzed. Goya is the first war reporter, their oils about the war against the French and the engravings on “The Disasters of War” are treated. Goya´s opinion about bullfighting is exposed denying the possibility that the painter was the first anti-bullfighting.